Structural phase transition and spontaneous exchange bias in NiCr1.9Fe0.1O4 nanoparticles: XRD, EXAFS and magnetic measurements. Issue 11 (1st August 2019) - Pandey, G.C.; Aquilanti, G.; Sastry, P.U.; Rath, C.
Abstract: Here, we report structural and magnetic phase transitions in NiCr1.9 Fe0.1 O4 nanoparticles of size ∼60 nm synthesized through cost-effective co-precipitation route. X-ray diffraction pattern shows a stable cubic phase at RT in contrast to tetragonal phase in bulk NiCr2 O4 . Decreasing the temperature, a complete tetragonal symmetry is observed at 50 K, while a coexistence of cubic and tetragonal phases in the intermediate temperature range. Interestingly, no tetragonal to orthorhombic phase transformation has been observed down to 12 K as observed in NiCr2 O4 at 70 K. The local structure examined from temperature dependent EXAFS demonstrates that although no change in distribution of cations among tetrahedral (A) and octahedral (B) sites down to 10 K has been observed, Fe 3+ ions occupy A site replacing equivalent amount of Ni 2+ towards B site which is contradicting to the bulk NiCr2 O4 where Ni 2+ occupies only A site. Magnetic studies demonstrate a two-fold increase in para to long-range ferrimagnetic transition, TC, due to increase in A-B exchange interaction and no change in spiral ordering temperature, TS indicates strong B-B interaction. In addition, these nanoparticles exhibit unusually high spontaneous exchange bias of ∼1.265 kOe at 60 K. We discuss the temperature dependent exchange bias on the basis of competition between uncompensated B site moments and ferromagnetically ordered spins at A site. The tunable exchange bias without field highlight the potential applications of these materials in spintronics devices.